Opposition from within – Israeli soldiers resist the occupation. Issue 3 (1st September 2020) - Hallward, Maia; Tuschling, Lina
ABSTRACT: Protests in response to Israeli military action in the Occupied Territories have a long history in Israel. While such opposition movements in many countries are comprised of civil society activists, the dynamics of protest differ in Israel because of the country's mandatory military service. From the 1980s to present day, former and current Israeli soldiers have used a wide range of methods, tactics, and strategies to challenge Israeli military actions. Using insights from nonviolent resistance theories, we examine how the approaches and goals of military opposition groups in Israel have changed over the past decades. Specifically, we develop a typology to explain why different types of protest arise from within the Israeli Defense Force that garner strong reactions – whether laudatory or derogatory – from the Israeli government and general public. The paper concludes with lessons learned for military opposition movements in the context of nonviolent resistance theory and practice.